Microbiology of Prosthetic Joint Infections: A Retrospective Study of an Italian Orthopaedic Hospital - Virginia Suardi; Daniele Baroni; Abdelrahman Hosni Abdelhamid Shahein; Valentina Morena; Nicola Logoluso; Laura Mangiavini; Antonio Virgilio Pellegrini (MDPI AG, 2024)
The most frequent cause of periprosthetic infections (PJIs) is intraoperative contamination; hence, antibiotic prophylaxis plays a crucial role in prevention. Modifications to standard prophylaxis can be considered if there is a high incidence of microorganisms resistant to current protocols. To date, very few studies regarding microbial etiology have been published in Italy. In this single-center, retrospective study conducted at IRCCS Ospedale Galeazzi-Sant'Ambrogio in Milan, we analyzed hip, knee, and shoulder PJIs in patients undergoing first implantation between 1 January 17 and 31 December 2021. The primary aim was to derive a local microbiological case history. The secondary aim was to evaluate the adequacy of preoperative antibiotic prophylaxis in relation to the identified bacteria. A total of 57 PJIs and 65 pathogens were identified: 16 S. aureus, 15 S. epidermidis, and 10 other coagulase-negative staphylococci (CoNS), which accounted for 63% of the isolations. A total of 86.7% of S. epidermidis were methicillin-resistant (MRSE). In line with other case reports, we found a predominance of staphylococcal infections, with a lower percentage of MRSA than the Italian average, while we found a high percentage of MRSE. We estimated that 44.6% of the bacteria isolated were resistant to cefazolin, our standard prophylaxis. These PJIs could be prevented by using glycopeptide alone or in combination with cefazolin, but the literature reports conflicting results regarding the adequacy of such prophylaxis. In conclusion, our study showed that in our local hospital, our standard antibiotic prophylaxis is ineffective for almost half of the cases, highlighting the importance of defining specific antibiotic guidelines based on the local bacterial prevalence of each institution.